PENGARUH MIRROR EXERCISE DAN MASSAGE PADA LAGHOPTHALMUS e.c LESI NERVUS FACIALIS - Kuswardani .; Akhmad Alfajri Amin; Meffananda Agrieta Fauziah (Universitas Widya Husada Semarang, 2020)
Background : Laghopthalmus is a condition where the eyelids cannot close properly. This disorder results from paralysis m.orbicularis. Eyeballs that protrude slightly outward resulting in blocked palpebrae closure. This disorder causes trauma to the conjunctiva and cornea, so that the conjunctiva and clear membranes become dry and infection occurs. Research Methods : This research method is experimental, research design uses case studies, and data collection techniques use Pre and Post Test. The sampling technique uses accidental sampling. Examination of facial motor functions using the ugo fisch scale, examination of muscle strength using MMT, and examination of the eye gap using midline. After 6 times mirror exercise and massage interventions, the result is that functional activities close to the eyes increase, dextra eye gap decreases and muscle strength m. Frontalis, m. Supercili corrugator, and m. Orbicularis Oculi increases. Result : The results obtained from this study can be concluded from mirror exercise and massage on laghopthalmus et causa facial nerve lesions are effective in improving motor function and increasing muscle strength.